Guesswork? Resolving Vagueness in User-Generated Software Requirements - Geierhos, Michaela; Bäumer, Frederik Simon (Partiality and Underspecification in Information, Languages, and Knowledge)
In recent years, there has been a proliferation of technological developments that incorporate processing of human language. Hardware and software can be specialized for designated subject areas, and computational devices are designed for a widening variety of applications. At the same time, new areas and applications are emerging by demanding intelligent technology enhanced by the processing of human language. These new applications often perform tasks which handle information, and they have a capacity to reason, using both formal and human language. Many sub-areas of Artificial Intelligence demand integration of Natural Language Processing, at least to some degree. Furthermore, technologies require coverage of known as well as unknown agents, and tasks with potential variations. All of this takes place in environments with unknown factors. The book covers theoretical work, advanced applications, approaches, and techniques for computational models of information, reasoning systems, and presentation in language. The book promotes work on intelligent natural language processing and related models of information, thought, reasoning, and other cognitive processes. The topics covered by the chapters prompt further research and developments of advanced systems in the areas of logic, computability, computational linguistics, cognitive science, neuroscience of language, robotics, and artificial intelligence, among others.

Studying Software Descriptions in SourceForge and App Stores for a better Understanding of real-life Requirements - Bäumer, Frederik Simon; Dollmann, Markus; Geierhos, Michaela (Proceedings of the 2nd ACM SIGSOFT International Workshop on App Market Analytics)
Users prefer natural language software requirements because of their usability and accessibility. Many approaches exist to elaborate these requirements and to support the users during the elicitation process. But there is a lack of adequate resources, which are needed to train and evaluate approaches for requirement refinement. We are trying to close this gap by using online available software descriptions from SourceForge and app stores. Thus, we present two real-life requirements collections based on online-available software descriptions. Our goal is to show the domain-specific characteristics of content words describing functional requirements. On the one hand, we created a semantic role-labeled requirements set, which we use for requirements classification. On the other hand, we enriched software descriptions with linguistic features and dependencies to provide evidence for the context-awareness of software functionalities.

On the origin of annotations: A module-based approach to representing annotations in the Natural Language Processing Interchange Format (NIF) - Menke, Peter; Ell, Basil; Cimiano, Philipp (Applied Ontology)

Indikatorbasierte Erkennung und Kompensation von ungenauen und unvollständig beschriebenen Softwareanforderungen - Bäumer, Frederik Simon
The vision of OTF Computing is to have the software needs of end users in the future covered by an automatic composition of existing software services. Here we focus on natural language software requirements that end users formulate and submit to OTF providers as requirement specifications. These requirements serve as the sole foundation for the composition of software; but they can be inaccurate and incomplete. Up to now, software developers have identified and corrected these deficits by using a bidirectional consolidation process. However, this type of quality assurance is no longer included in OTF Computing - the classic consolidation process is dropped. This is where this work picks up, dealing with the inaccuracies of freely formulated software design requirements. To do this, we developed the CORDULA (Compensation of Requirements Descriptions Using Linguistic Analysis) system that recognizes and compensates for language deficiencies (e.g., ambiguity, vagueness and incompleteness) in requirements written by inexperienced end users. CORDULA supports the search for suitable software services that can be combined in a composition by transferring requirement specifications into canonical core functionalities. This dissertation provides the first-ever method for holistically recording and improving language deficiencies in user-generated requirement specifications by dealing with ambiguity, incompleteness and vagueness in parallel and in sequence.

Narrative Ethics and Dementia in Alice LaPlante’s Turn of Mind - Strauß, Sara (Dementia and Subjectivity. Aesthetic, Literary and Philosophical Perspectives)

Introduction - Strauß, Sara (Dementia and Subjectivity. Aesthetic, Literary and Philosophical Perspectives)

Neuroethical Reflections on Body and Awareness in Kazuo Ishiguro’s Never Let Me Go and Ian McEwan’s Saturday - Strauß, Sara (Presence of the Body: Awareness In and Beyond Experience)

The Immobility of Power in British Political Theatre after 2000: Absurdist Dystopias - Tönnies, Merle (Journal of Contemporary Drama in English)

Still/Again 'Political'? New Approaches to Questioning Power in Mike Bartlett's 13 (2011) - Tönnies, Merle (Finance, Terror, and Science on Stage. Current Public Concerns in 21st-Century British Drama)

Pope, G.: Reading London's Suburbs - Tönnies, Merle (Anglistik. International Journal of English Studies)

From User Demand to Software Service: Using Machine Learning to Automate the Requirements Specification Process - van Rooijen, Lorijn; Bäumer, Frederik Simon; Platenius, Marie Christin; Geierhos, Michaela; Hamann, Heiko; Engels, Gregor (2017 IEEE 25th International Requirements Engineering Conference Workshops (REW))
Bridging the gap between informal, imprecise, and vague user requirements descriptions and precise formalized specifications is the main task of requirements engineering. Techniques such as interviews or story telling are used when requirements engineers try to identify a user's needs. The requirements specification process is typically done in a dialogue between users, domain experts, and requirements engineers. In our research, we aim at automating the specification of requirements. The idea is to distinguish between untrained users and trained users, and to exploit domain knowledge learned from previous runs of our system. We let untrained users provide unstructured natural language descriptions, while we allow trained users to provide examples of behavioral descriptions. In both cases, our goal is to synthesize formal requirements models similar to statecharts. From requirements specification processes with trained users, behavioral ontologies are learned which are later used to support the requirements specification process for untrained users. Our research method is original in combining natural language processing and search-based techniques for the synthesis of requirements specifications. Our work is embedded in a larger project that aims at automating the whole software development and deployment process in envisioned future software service markets.
Keywords: Software; Unified modeling language; Requirements engineering; Ontologies; Search problems; Natural languages

Dementia and Subjectivity. Aesthetic, Literary and Philosophical Perspectives

Fragments of a Life Remembered: Fragmentation and Silences in Dementia Narratives - Strauß, Sara (Narrative and Mental Health)

Semantic Annotation of Software Requirements with Language Frame - Kim, Yeong-Su; Lee, Seung-Woo; Dollmann, Markus; Geierhos, Michaela (International Journal of Software Engineering for Smart Device)
An end user generally writes down software requirements in ambiguous expressions using natural language; hence, a software developer attuned to programming language finds it difficult to understand th meaning of the requirements. To solve this problem we define semantic categories for disambiguation and classify/annotate the requirement into the categories by using machine-learning models. We extensively use a language frame closely related to such categories for designing features to overcome the problem of insufficient training data compare to the large number of classes. Our proposed model obtained a micro-average F1-score of 0.75, outperforming the previous model, REaCT.
Keywords: Natural Language Processing; Semantic Annotation; Machine Learning

The Renewal of British Political Theater in the Twenty-First Century: Indirect Narrative Approaches to Ideology and Power - Tönnies, Merle (Storyworlds: A Journal of Narrative Studies)

Ansprache - Peckhaus, Volker (Verleihung der Ehrendoktorwürde an den Herrn Bundesminister des Auswärtigen Dr. Frank-Walter Steinmeier durch die Fakultät für Kulturwissenschaften am 29. Dezember 2016)

Geschlechter-Macht-Binarismen relativiert: Margaret Atwoods Männerdarstellungen in "The Handmaid's Tale" - Hannebohm, Ronja (Geschlechter-Dramen: literarische und filmische Inszenierungen von 1800 bis heute)

„Nichts mehr stimmt, und alles ist wahr.“ Tabubrüche in Herta Müllers Atemschaukel - Willeke, Stephanie (Ästhetik des Tabuisierten in der Literatur- und Kulturgeschichte)

Shoah und Gulag - Willeke, Stephanie (Herta Müller-Handbuch)

Das Radikale – gesellschafts-politische und formal-ästhetische Aspekte. Eine Einführung - Willeke, Stephanie (Das Radikale – gesellschafts-politische und formal-ästhetische Aspekte in der Gegenwartsliteratur)

Konstruierte Wahrheiten. Benjamin Steins Die Leinwand - Willeke, Stephanie (Das Radikale. Gesellschafts-politische und formal-ästhetische Aspekte in der Gegenwartsliterstur)

Das Radikale. Gesellschafts-politische und formal-ästhetische Aspekte in der Gegenwartsliterstur

„Formzerstörtes Formgebären. ‚Arbeit der Formen‘ in Elisabeth Langgässers Der Torso“ - Böker, Ines (Das Radikale. Gesellschaftspolitische und formal-ästhetische Aspekte in der Gegenwartsliteratur)

Wie nehmen neu zugewanderte Menschen in Deutschland ihre sprachliche Umgebung wahr? Zum Umgang von Deutschlernenden mit Text-Bild-Kombinationen im Alltag - Dresing, Pirkko; Bechauf, Carina; Möllenkamp, Mareike; Ballweg, Sandra; Grubert, Julia; Lewicki, Anja (DaZu und DaFür - Neue Perspektiven für das Fach Deutsch als Zweit- und Fremdsprache zwischen Flüchtlingsintegration und weltweitem Bedarf. 43. Jahrestagung des Fachverbandes Deutsch als Fremd- und Zweitsprache an der Universität Duisburg-Essen 2016)

Lernendenautonomie und Portfolioarbeit? Zum selbstbestimmten Handeln von Studierenden bei der Portfolioarbeit im DaF-Unterricht - Ballweg, Sandra (Inhalt und Vielfalt – Neue Herausforderungen für das Sprachenlernen und -lehren an Hochschulen. Erträge des 5. Bremer Symposions)

Das DaZ-Modul in der Lehrerausbildung. Ideen zur Gestaltung von Übungen, Seminaren und Vorlesungen

Unterrichten neu zugewanderter Schüler*innen im Fachunterricht an berufsbildenden Schulen – Anforderungen und Ressourcen - Dohmann, Olga; Havkic, Amra; Domenech, Madeleine; Niederhaus, Constanze (Mehrsprachigkeit: Spracherwerb, Unterrichtsprozesse, Schulentwicklung. Beiträge zum 11. Workshop Kinder und Jugendliche mit Migrationshintergrund)

Lenzen, Wolfgang, “Leibniz’s Logic and the ‘Cube of Opposition’”, In: Logica Universal-is 10 (2016), 171–189 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Morscher, Edgar, "Bernard Bolzanos Lehre von Grund und Folge. Eine axiomatische Rekonstruktion", Academia Verlag: Sankt Augustin 2016 (Beiträge zur Bolzano-Forschung; 37) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Tho, Tzuchien, "Vis vim vi: Declinations of Force in Leibniz’s Dynamics", Springer: Cham 2017 (Studies in History and Philosophy of Science; 46) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Centrone, Stefania, "Studien zu Bolzano", Academia: Sankt Augustin 2015 (Beiträge zur Bolzano-Forschung; 26) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Casari, Ettore, "Bolzano’s Logical System", Oxford University Press: Oxford 2016 (Oxford Logic Guides; 54) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

de Rouilhan, Philippe, “Tarski’s Recantation: Reading the Postscript to ‘Wahrheitsbegriff’”, in F.F. Abeles and M.E. Fuller (eds.), Modern Logic 1850–1950, East and West, Birhäuser/Springer: Cham 2016 (Stud. Univ. Log.), 119–134 - Peckhaus, Volker (Mathematical Reviews)

Chemla, Karine, “Historiography and History of Mathematical Proof: A Research Programme”, in K. Chemla (ed.), The History of Mathematical Proof in Ancient Traditions, Cambridge University Press: Cambridge 2015, 1–68 - Peckhaus, Volker (Mathematical Reviews)

Caminada, Martin W.A., Dvořák, Wolfgang, und Vesic, Srdjan, “Preferred Semantics as Socratic Discussion”, In: J. Logic Comput. 26 (2016), no. 4, 1257–1292 - Peckhaus, Volker (Mathematical Reviews)

Rosado Haddock, Guillermo E., “The Interplay between Logic, Mathematics and Philosophy”, In: South African Journal of Logic 2 (2016), 41–66 - Peckhaus, Volker (Mathematical Reviews)

Doherty, Fiona T., “Hilbert on Consistency as a Guide to Mathematical Reality”, In: Logique & Analyse 237 (2017), 107–128 - Peckhaus, Volker (Mathematical Reviews)

Videokonfrontation als Methode für die angewandte Schreibforschung. Zwischen Investigation und Intervention - Karsten, Andrea (Qualitative Methoden in der Schreibforschung)

Zwei Varianten qualitativer Textanalyse zur Identifikation von Stimme(n) in Texten - Karsten, Andrea; Stock, Ingrid (Qualitative Methoden in der Schreibforschung)

Der Bodybuilder als autoritärer Charakter. Das “neue Dreß“ des nationalsozialistischen Körperkults in Elfriede Jelineks Ein Sportstück (1998) - Tönsing, Johanna (Colloquia Germanica 3-4 (2017) Special Issue: New Authorities in Politics and Literature)

Begehren, Macht und Raum. 'Die halbe Birne' Konrads von Würzburg - Musiol, Marie-Luise (Abenteuerliche ›Überkreuzungen‹ Vormoderne intersektional)

„ey saelec wîp, fürht ir mich?“ - Die Figur der armen Witwe in Reinbots von Durne Der heilige Georg aus einer intersektionalen Perspektive - Somogyi, Peter (Abenteuerliche ‘Überkreuzungen‘. Vormoderne intersektional (Aventiuren 12))

Sprachtherapie mit Kindern

Klaus Kordon. Bielefelder Poet in Residence 2016 / Paderborner Kinderliteraturtage 2017

"If I Were King!" Morals and Physics in Emilie Du Châtelet’s Subtle Thoughts on Liberty - Hagengruber, Ruth Edith (Women and Liberty)

Creative Algorithms and the Construction of Meaning - Hagengruber, Ruth (Berechenbarkeit der Welt?)

Bergès, Sandrine; Coffee, Alan (Eds.). The Social and Political Philosophy of Mary Wollstonecraft. Oxford University Press, 2017. - Hagengruber, Ruth Edith

Interesse wecken für einen engagierten Autor und (sein) problemorientiertes Schreiben - Paderborner Grundschulklassen werden auf die Begegnung mit Klaus Kordon vorbereitet - Kruse, Iris; Terhorst , Sarah (Klaus Kordon.Bielefelder Poet in Residence 2016 / Paderborner Kinderliteraturtage 2017)

Lesen, um zu schreiben. Grundschulunterricht Deutsch

Wir verlängern das Buch. Episodisch erzählte Geschichten weiterschreiben - Kruse, Iris; Terhorst , Sarah (Grundschulunterricht Deutsch)